Implementasi dan Analisis Attack Tree pada Aplikasi DVWA Berdasar Metrik Time dan Probability - Irawan, Alfian Rifki; Widjajarto, Adityas; Fathinuddin, Muhammad (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The formulation of attack trees can be based on the exploitation stages in web-based applications. According to this formulation, this research aims to understand the relationship between attack trees and exploitation characteristics using time and probability metrics. The construction of attack trees is based on experimental platforms using the DVWA web-based application, both in protected and unprotected conditions by a Web Application Firewall (WAF). Exploitation is carried out on five vulnerabilities, namely SQL Injection, XSS (Reflected), Command Injection, CSRF, and Brute Force. The analysis results without a WAF show that the Cross-Site Request Forgery attack tree occupies the top position with a score of 18.19. On the other hand, the Brute Force attack tree ranks last with a score of 230.09. With the presence of a WAF, the Command Injection attack tree takes the first position with a score of 4.80, while the Brute Force attack tree remains in the last position with a score of 43.08. Further research in this study may involve a detailed examination of probability metrics and the calculation of vulnerability factors.